Going Beyond Clinical Care to Reduce Health Care Spending: Findings From the J-CHiP Community-based Population Health Management Program Evaluation. Issue 7 (July 2018) - Murphy, Shannon M.E.; Hough, Douglas E.; Sylvia, Martha L.; Sherry, Melissa; Dunbar, Linda J.; Zollinger, Raymond; Richardson, Regina; Berkowitz, Scott A.; Frick, Kevin D.
Abstract : Background: Addressing both clinical and nonclinical determinants of health is essential for improving population health outcomes. In 2012, the Johns Hopkins Community Health Partnership (J-CHiP) implemented innovative population health management programs across acute and community environments. The community-based program involved multidisciplinary teams [ie, physicians, care managers (CM), health behavior specialists (HBS), community health workers, neighborhood navigators] and collaboration with community-based organizations to address social determinants. Objectives: To report the impact of a community-based program on cost and utilization from 2011 to 2016. Design: Difference-in-difference estimates were calculated for an inclusive cohort of J-CHiP participants and matched nonparticipants. The analysis was replicated for participants with a CM and/or HBS to estimate the differential impact with more intensive program services. Subjects: A total of 3268 high-risk Medicaid and Medicare beneficiaries (1634 total J-CHiP participants, 1365 with CM and 678 with HBS). Outcome Measures: Paid costs and counts of emergency department visits, admissions, and readmissions per member per year. Results: For Medicaid, costs were almost $1200 per member per year lower for participants as a whole, $2000 lower for those with an HBS, and $3000 lower for those with a CM; hospital admission and readmission rates were 9%–26% lower for those with a CM and/or HBS. For Medicare, costs were lower (−$476), but utilization was similar or higher than nonparticipants. None of the observed Medicaid or Medicare differences were statistically significant. Conclusions: Although not statistically significant, the results indicate a promising innovation for Medicaid beneficiaries. For Medicare, the impact was negligible, indicating the need for further program modification. Abstract : Supplemental Digital Content is available in the text.